Water spirits within the fishers' worldview: implications for fishing management in Northeast Brazil - André Bastos da Silva; João Batista Lopes; Luciano Silva Figueiredo; Roseli Farias Melo de Barros; Wedson Medeiros Silva Souto; Nelson Leal Alencar; Clarissa Gomes Reis Lopes (BMC, 2019)
Abstract Background Historically, aquatic environments are linked to the worldview of many local people, where there is an interconnection between the natural world, the supernatural, and the social organization. In this study, we provided a discussion on how the supernatural beings that inhabit the freshwater systems interact with artisanal fishers and fishing resources in the riverine community of Parnaíba River middle course, in Mid North of Northeast Brazil. We also provided the implications of these interactions on the fisher's behaviors and how the acculturation process (e.g., introduction of new religions) can affect the fishers' worldview. Method The selection of participants was done through intentional sampling. The content qualitative analysis was carried out to interpret the data from semi-structured interviews with 29 artisanal fishers. Results The mythical representations that inhabit the aquatic environments in the surveyed area were as follows: Mãe d' água, Cabeça de cuia, Muleque d'água, Visage, Piratinga, Sucuiuiu, and Luz e Arco-íris. These beings have distinctions regarding the form and attributions and can be associated with seasonality (temporal markers) and specific habitats (spatial markers). The respect and fear feeling of the mythical beings were striking among the fishers interviewed. For instance, we have record offering practices in order to obtain protection and success during the fisheries. These practices suggest that there may be local conservationist habits in fisheries management. However, the advancement of urbanization and the introduction of new religions that deny the existence of mythical entities are factors that can generate the acculturation process among the fishers. Conclusions It is therefore necessary to carry out more studies in the surveyed area in order to evaluate the existence of possible patterns in the relationship between fisher and mythical beings. This information could confirm the role of mythical beings as environmental regulators. Consequently, it could be considered in the conservationist policies of fishery resources, reinforcing the importance of local knowledge and cultural factors for fishing management approaches.